Metabolic and Haematological Profile of Infants Born to Gestational and Pregestational Diabetic Mothers (Bangladesh Journal of Child Health, 2020)
Background: Diabetes mellitus is the most common metabolic disorder complicating pregnancy. Infants of diabetic mothers (IDMs) are prone to develop complications during early neonatal period. The study was undertaken to describe and compare the metabolic and haematological parameter of infants born to gestational (GDM) and pregestational (PGDM) diabetic mothers.Meterials and Methods: The hospital based prospective study was conducted at special care neonatology unit of Dr. M. R. Khan Shishu Hospital & ICH from January 2018 to December 2018. Blood samples were collected to perform relevant biochemical and haematological tests.Results: Of the 68 neonates, 61.8% were born to mothers with GDM and 38.2% were born to mothers with PGDM. In case of GDM, 4.8% were Small for Gestational Age (SGA), 61.9% were Appropriate for Gestational Age (AGA) and 33.3% were Large for Gestational Age (LGA). Hypoglycemia occurred in 71.4% of neonates with GDM and 53.8% of neonates with PGDM. Hypocalcemia was observed in 47.6% of neonates with GDM and 69.2% of neonates with PGDM. Frequency of hypoglycemia, polycythemia and hyperbilirubinemia were significantly higher in neonates born to mothers with GDM (p value 0.01, 0.02 and < 0.001 respectively) and frequency of hypocalcemia was significantly higher in neonates born to mothers with PGDM (p value 0.02).Conclusions: The frequency of hypoglycaemia, polycythemia and hyperbilirubinemia were significantly more in newborns of GDM compared to infants of PGDM but the frequency of hypocalcemia was significantly more in newborns of PGDM.Bangladesh J Child Health 2020; VOL 44 (2) :82-86